2010
DOI: 10.1075/is.11.2.22tho
|View full text |Cite
|
Sign up to set email alerts
|

The face-to-face light detection paradigm

Abstract: We introduce a novel paradigm for studying the cognitive processes used by listeners within interactive settings. This paradigm places the talker and the listener in the same physical space, creating opportunities for investigations of attention and comprehension processes taking place during interactive discourse situations. An experiment was conducted to compare results from previous research using videotaped stimuli to those obtained within the live face-to-face task paradigm. A headworn apparatus is used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Moreover, they did not control for stimulus complexity in the primes, adding to the difficulty of interpreting their result. An LVF effect of emotional interference was also reported by Thompson et al (2009), who measured speeded detection of a single dot appearing on a static face while participants listened to emotional versus nonemotional speech. They reported slowed responses to LVF, but not RVF, dot presentations when emotional, but not nonemotional, prosody was concurrent in the speech stream, suggesting that lateralized emotional interference effects may operate cross-modally.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, they did not control for stimulus complexity in the primes, adding to the difficulty of interpreting their result. An LVF effect of emotional interference was also reported by Thompson et al (2009), who measured speeded detection of a single dot appearing on a static face while participants listened to emotional versus nonemotional speech. They reported slowed responses to LVF, but not RVF, dot presentations when emotional, but not nonemotional, prosody was concurrent in the speech stream, suggesting that lateralized emotional interference effects may operate cross-modally.…”
Section: Discussionmentioning
confidence: 93%
“…The aim of our experiment was to test these possibilities. Two somewhat relevant previous studies reported an LVF performance decrement after or during exposure to emotional stimuli (Hartikainen, Ogawa, & Knight, 2000;Thompson, Malloy, Cone, & Hendrickson, 2009), but in both cases, such effects could have been due to eye movement biases, spatial attention shifts, or featural differences between emotional and nonemotional stimuli.…”
mentioning
confidence: 99%
“…First, there was a strong negative relationship between weight and mean temperature. This result suggests that red-backed fairy-wrens may conform to Bergmann’s rule, which posits that organisms will evolve to be smaller in hotter climates to enhance thermoregulation via a more favorable surface area to volume ratio [20,21]. Second, there was a strong positive relationship between tarsus length and percent tree cover, and longer tarsi may be an adaptation enabling the red-backed fairy-wren to better maneuver and forage in trees sensu [22].…”
Section: Discussionmentioning
confidence: 99%
“…Smaller numbers are also kept as pets on ‘hobby’ farms [1]. There are now in excess of 90,000 alpacas registered in Australia, with more than 90% of these being of the Huacaya breed [2].…”
Section: Introductionmentioning
confidence: 99%